Analisis Penggunaan Senjata Api di Tubuh Polri: Peraturan, Penyimpangan, dan Perubahan - Edi Saputra Hasibuan (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
In carrying out the demands of a profession that has many challenges, the National Police will certainly always intersect with the situation on the ground that makes them required to be ready and swift, especially regarding the handling and prevention of criminal acts, these conditions make every police member must be equipped with expertise and abilities in the process of their activities, in this case talking about the authority to own and use firearms, In general, members who serve in the field can use their weapons to warn against criminals, and under certain conditions, members can use their weapons to incapacitate the perpetrators, even to crack down on the spot (execution) of the perpetrators if they are life-threatening and ignore the warnings given. But this is a problem because there are people who use their authority for their own benefit and violate the law. This paper discusses how firearms actually use in the field, gun abuse cases, and what are the benchmarks for the use of firearms based on what has been regulated by relevant laws and rules.